2008
DOI: 10.1123/jsep.30.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Cognitive Theory to Predict Physical Activity in Inner-City African American School Children

Abstract: Researchers using social cognitive theory and employing built environment constructs to predict physical activity (PA) in inner-city African American children is quite limited. Thus, the purpose of our investigation was to evaluate the ability of important social cognitive variables (e.g., self-efficacy) and built environment constructs (e.g., neighborhood hazards) to predict African American children’s PA. Children (N = 331, ages 10–14) completed questionnaires assessing social cognitive theory constructs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 63 publications
7
35
0
1
Order By: Relevance
“…This result is consistent with a large body of earlier quantitative studies (Martin & McCaughtry, 2008;Martin et al, 2007;Park & Kim, 2008;Wang & Wang, 2015) that has demonstrated the influence of gender on children's leisure-time PA. For instance, in a systematic review (Park & Kim, 2008) of 35 cross-sectional and longitudinal studies on the determinants of PA in adolescents, female gender appeared to be negatively associated with PA in European, American and Asian youth populations. In these studies, the influence of gender appeared to be explained a complex interplay of developmental (e.g., pubertal phase), environmental (e.g equipment provided) and sociocultural (stereotypes) issues.…”
Section: Jpes ®supporting
confidence: 81%
See 1 more Smart Citation
“…This result is consistent with a large body of earlier quantitative studies (Martin & McCaughtry, 2008;Martin et al, 2007;Park & Kim, 2008;Wang & Wang, 2015) that has demonstrated the influence of gender on children's leisure-time PA. For instance, in a systematic review (Park & Kim, 2008) of 35 cross-sectional and longitudinal studies on the determinants of PA in adolescents, female gender appeared to be negatively associated with PA in European, American and Asian youth populations. In these studies, the influence of gender appeared to be explained a complex interplay of developmental (e.g., pubertal phase), environmental (e.g equipment provided) and sociocultural (stereotypes) issues.…”
Section: Jpes ®supporting
confidence: 81%
“…Percentages of explained variance demonstrate the high performance of the study to predict children's PA (42.1%) and intention (66%), corresponding to a strong effect size according to Cohen's criteria (Cohen, 1992) (f 2 ≥0.35). For comparison, in earlier prediction studies of young populations, the percentage of explained variance ranged between 8% and 30% for PA (Foley et al, 2008;Godin, Anderson, Lambert, & Desharnais, 2005;Hagger et al, 2002;Martin & McCaughtry, 2008;Martin, Shapiro, & Prokesova, 2013;Wang & Zhang, 2016) and between 28.7% and 56% for intention (Foley et al, 2008;Godin & Shephard, 1986;Hagger et al, 2002;Martin et al, 2007;Mummery et al, 2000;Wang & Zhang, 2016). In addition, the present study is also the first to specifically explore the psychosocial determinants of children's PA in the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Just as with parents, peer social support has been found to be a strong predictor of PA in inner-city African-American adolescents 7 and a predictor of dietary fat and fiber intake in ethnically diverse sixth graders. 10 Furthermore, sex differences in youth PA levels, 44,45 fruit and vegetable intake, 46,47 and attitudes toward health behaviors (e.g., boys find PA competition compelling while girls find it aversive 48 ) suggest peers may be more supportive of boys in relation to sports and more supportive of girls in relation to dietary change.…”
Section: Introductionmentioning
confidence: 99%
“…because positive outcomes in African-American youth across a variety of domains (e.g., academic, behavioral, health-related, social) have been shown to be influenced not only by extended family networks, 5,6,11 but by peer relationships 7,10 and a combination of both, 8,9 the influence of both parent and peer factors on adolescent health behaviors is examined in this study. Just as with parents, peer social support has been found to be a strong predictor of PA in inner-city African-American adolescents 7 and a predictor of dietary fat and fiber intake in ethnically diverse sixth graders.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, research conducted among African American youth in inner-cities has suggested social support was a more important predictor of PA [41] [42] [43]. Because youth PA is often determined by the interplay of these personal, environmental, and behavioral factors, this study focused on using SCT to analyze how all three factors were embedded in students' perspectives of yoga practice in a PE setting.…”
Section: Introductionmentioning
confidence: 99%